Metabólitos especiais dos galhos de Nectandra leucantha Nees & Mart. (LAURACEAE) e derivados semissintéticos – caracterização molecular, avaliação do potencial e mecanismo antitumoral contra o melanoma murino - Sousa, Fernanda Samara de [UNIFESP] (2018)
In this work, extracts from twigs of Nectandra leucantha (Lauraceae) displayed in vitro cytotoxic activity against murine melanoma tumorigenic cell line (B16F10). Thus, hexane extract of N. leucantha was subjected to chromatographic fractionation, which allowed the isolation of six neolignans: 1,2-dimethoxy-6-[2'-methoxy-4'-(8'-propenyl) phenoxy] -4-(8-propenyl) benzene (I), dehydrodieugenol B (II), 1,2-dimethoxy-6- [2'-methoxy-4 '- (8'-propenyl) phenoxy]-4-(7-hydroxy-8-propenyl) benzene (III), 1-hydroxy-2-methoxy-6- [2'-methoxy-4 '-(8'-propenyl) phenoxy]-4-(7- propenyl) benzene (IV), 1,2-dimethoxy-6- [2'-methoxy-4 '-(8'-propenyl) phenoxy]-4-(7-oxo-8-propenyl) benzene (V) and 2-methoxy-6-[2'-methoxy-4'-(8'-propenyl) phenoxy]-4-(7-oxo-8-propenyl) benzene (VI), of which V and VI are unpublished in the literature. Structures of substances I - VI were defined by spectroscopic and spectrometric methods. These compounds were evaluated for their cytotoxicity against SK-BR-3, HCT, U87-MG, A2058 and B16F10 tumorigenic lines. Among the compounds tested, the most active were II and VI, presenting IC50 values of 78.8 ± 2.8 and 82.2 ± 3.5 μM against B16F10, respectively. The mechanism of action of compounds II and VI against murine melanoma cell line showed both compounds can induce intrinsic apoptosis. Compound II induced caspase-3 and PARP activation, while compound VI acted deregulating Bcl-2 protein levels. These effects were accompanied by increased levels of reactive oxygen species, as a consequence of mitochondrial damage, followed by F-actin aggregation in the death process of these cells. In addition, compound II displayed oxidative properties, and both compounds, especially VI, displayed potential to alkylate nucleophiles, suggesting an accessory mechanism of cytotoxicity induction, by these metabolites. For structure-activity relationship (SAR) studies, 24 semisynthetic derivatives were prepared from I and II, and their respective IC50 values were also determined against B16F10. Derivatives 2a (2-methoxy-6-(2-methoxy-4-propylphenoxy)-4-propylphenol), 2h (2-methoxy-6-(2-methoxy-4-propylphenoxy)-4-propylphenyl acetate) and 3h (5-(cyclopropylmethyl)-1-(4-(cyclopropylmethyl)-2-methoxyphenoxy)-2,3-dimethoxybenzene) were the most active compounds, presenting IC50 values of 53.3 ± 2.4, 51.8 ± 1.6 and 59.3 ± 3.2 μM, respectively, suggesting that the hydrogenation (2a), hydrogenation/acetylation (2h) and epoxidation (3h) cause an increase in the antitumor potential of natural products I and II. The 4-OAc, 4-OH and 1-bezyloxirane groups of the tested structures were chosen as the most important, by their statistical impact at cytotoxicity. For the selected position, bioisosteres substituents were applied. The results suggested that, some projected neolignans by prediction methods achieved lower IC50 than semi-synthetic derivatives, pointing them as promising candidates for synthesis.